Communication Planning Of The Dayah Jamiah Al-Aziziyah Batee Iliek Organization In Preparing Da'i Cadres - Muhibudin Muhibudin; Mohd. Hatta; Yusnadi Yusnadi (International Journal Of Education, Social Studies, And Management (IJESSM), 2022)
This Research aim to analyze (a) the process of the communication planning Dayah Jamiah Al-Aziziyah in preparing the Da’i candidate. (b) the implementation of the communication planning Dayah Jamiah Al-Aziziyah in prepare ng the Da’i candidate, (c) the implication of the communication planning Dayah Jamiah Al-Aziziyah in preparing the Da’i candidate. This research used constructivism paradigm to acquire understanding development of communication planning in preparing the Da’i candidate in Dayah Jamiah Al-Aziziyah, so that helps the interpretasion process towards this event. Qualitative approach was used in this research. Data Source of this reasearch; primary data and secondary data. Primary data obtained from interviews, observation and study of documents as well as behavior obtained from research subjects related to communication planning in preparing candidate of Da’i. the informant: 1) The Leader Dayah Jamiah Al-Aziziyah; 2) Dayah  Educator and Administrator; 3) Chairman of the students organization or Senior students; 4) Students of  Dayah Jamiah Al-Aziziyah. Form the informant next developed to find another information by using snowball technique (snowball sampling). While the secondary data is in the form of writings, recording,images or pictures related with the process of activity corresponded with communication planing. The result shows that communication planning in preparing the Da’i candidate are three steps to take: 1). The communication planning stage. In preparing the candidate of Da’i carried out audience analysis, goal setting, media selection, message design, program evaluation. 2). Implementation of communication planning. The early development of the students was equipped with an understanding of religious knowledge and Turast books. Students muhadarah watched by mudabbir. Evaluation of muhadarah shows an indication of having achieved success in a good category. 3) The implication of communication planning shows that students of Dayah Jamiah Al-Aziziyah won second place in Bireuen Regency in a speech competition and were able to make short films, youtuber. this shows that Dayah Jamiah Al-Aziziyah has been able to create santri who are ready to compete in every race.